Peran dan model entrepreneurial leadership kepala sekolah dalam inovasi pendidikan kewirausahaan SMK - Tiara Aprillia; Halimatus Sadiyah; Sumarno Sumarno; Henny Indrawati; Caska Caska (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to analyze the concept, role, and model of entrepreneurial leadership among vocational high school (VHS) principals in promoting innovation in entrepreneurship education. The study employed an Integrative Literature Review (ILR) through the identification, selection, quality assessment, and thematic synthesis of 13 national and international articles published between 2014 and 2026 and retrieved from Google Scholar, Scopus, and Garuda. The findings reveal four key dimensions of entrepreneurial leadership: risk-taking, opportunity-seeking, resource mobilization, and innovation driving. These dimensions are manifested through teacher empowerment, the development of teaching factories and industry partnerships, cross-sectoral networking, entrepreneurship-oriented curriculum innovation, and the optimization of school resources and autonomy. The study proposes a conceptual model linking entrepreneurial leadership dimensions, educational innovation mechanisms, and graduate outcomes, including work readiness, entrepreneurial mindset, and competitiveness. Its novelty lies in integrating these three components into a comprehensive conceptual framework.